Qualidade de vida, estado nutricional e fatores associados: um estudo em usuários de serviços de hemodiálise da região metropolitana da Grande Vitória-ES - Barreto, Marina Abelha (2021)
The advance of Chronic Kidney Disease (CKD) is a major public health problem, with an increase of 58% in the last 10 years. The high prevalence is accompanied by an increase in the number of users of hemodialysis (HD) services, performed by 92% of individuals. In addition to the low socioeconomic level of the population on HD that contributes to worse health outcomes, individuals on HD are subject to several hemodynamic and metabolic changes, of the disease and treatment, leading to changes in nutritional status and clinical complications, which directly affect the quality of life. life (QOL). Since HD prolongs the lives of its users, QOL has become an important measure of health outcome, directed at the perception of physical, psychological and social limitations, influenced by the disease, by treatment. Therefore, the aim of this study was to assess the association between QoL and sociodemographic, clinical, lifestyle and nutritional status factors. QOL was assessed using the SF-36 questionnaire (Short-Form SF-36), structured in 36 items, subdividing QOL into 8 domains and summarized into 2 components (physical and mental), with scores from 0 to 100. Previous To collect data, a pilot study was conducted, with the participation of 57 users of the HD service, in order to assess the internal consistency and reproducibility of the questionnaire. Subsequently, this study was carried out, being a cross-sectional, observational study, in all HD clinics in the Metropolitan Region of Grande Vitória / ES, totaling 11 clinics and composed of 1,024 users of HD services. The worst QOL was portrayed by the physical aspect domain (26.78) and the QOL by the mental health domain (72.16). Of the sociodemographic characteristics, lifestyle, clinical and nutritional status measures studied, the male gender, age group, physical activity, number of intradialitic complications and serum albumin, associated with QOL, stand out after adjusting for the study variables, configuring themselves as the predictors of QL, both physical and mental, of this population. It is concluded, therefore, that several factors impact the QOL of individuals on HD and, therefore, assessing QOL becomes essential. It is noteworthy that QOL was associated with simple and viable measures for clinical practice, such as monitoring nutritional status, encouraging physical activity and preventing the reduction of the number of intradialitic complications, therefore modifiable factors that guarantee a better outcome of health, since the low QOL is one of the main problems of this population.